Catalytic conversion and chemical recovery - Hafeez, Sanaa; Pallari, Elena; Manos, George; Constantinou, Achilleas (My University, 2019)
Polymers are large molecules, whether natural or synthetic, that are brought together through polymerization and give rise to a wide range of products and applications in the manufacturing, medical, engineering, fashion, and aviation sector. The increase in the world’s demand for polymers has led to an accumulation of plastic waste in the environment, specifically in landfills, that has serious consequences to human and animal health. The nonbiodegradable nature of synthetic polymers has produced the need for more sustainable and efficient waste processing methods like pyrolysis. Pyrolysis is a chemical process that treats plastic waste with thermal energy to recover desirable products such as fuels for energy and chemical feedstocks. This process has attracted a lot of attention due to the fact that it does not produce harmful gases, and has lower carbon monoxide and dioxide emissions when compared to other plastic solid waste (PSW) methods. In this work, the catalytic and noncatalytic methods are discussed along with an in-depth review of the different techniques used in the pyrolysis process. The operation variables effect is also discussed, as well as the different reactor types. A review of different processing and co-processing methods is also highlighted.
Keywords: Polymers; Waste; Recovery; Recycling; Conversion; Pyrolysis; Catalysts; Energy